2019
DOI: 10.13075/mp.5893.00822
|View full text |Cite
|
Sign up to set email alerts
|

A job crafting measure: psychometric properties of the Polish version of the <i>Job Crafting Scale</i>

Abstract: Wstęp: Zmienna przekształcanie pracy (job crafting) od kilkunastu lat jest obiektem rosnącego zainteresowania badaczy i praktyków. Dotyczy ona zachowań polegających na dopasowywaniu właściwości pracy przez pracownika tak, by praca odpowiadała jego zdolnościom i potrzebom. Celem artykułu jest analiza właściwości psychometrycznych polskiej wersji skali Job Crafting Scale (JCS), która służy do pomiaru tej zmiennej. Materiał i metody: Skala JCS w wersji oryginalnej składa się z 21 pozycji testowych tworzących 4 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…As it can be seen from exploratory factor analysis, the number and structure of the components of the 21-item JCS almost perfectly correspond to the initial version of the JCS (Tims et al, 2012). The same number and structure of the components was also found within other national validation studies (e.g., Akın et al, 2014;Bakker et al, 2018;Rogala & Cieślak, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As it can be seen from exploratory factor analysis, the number and structure of the components of the 21-item JCS almost perfectly correspond to the initial version of the JCS (Tims et al, 2012). The same number and structure of the components was also found within other national validation studies (e.g., Akın et al, 2014;Bakker et al, 2018;Rogala & Cieślak, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Job crafting, represented through these three dimensions, correlated positively with work self-efficacy, work engagement and job performance. The Polish version of the JCS also replicated the four-factor structure of the original JCS, with satisfactory reliability and validity (Rogala & Cieślak, 2019). Likewise, the Turkish validation of the JCS (Akın et al, 2014) revealed a satisfactory fit of the four-factor solution, as well as good reliability coefficients for each dimension.…”
Section: Theoretical and Research Backgroundmentioning
confidence: 60%
See 1 more Smart Citation
“…Job crafting, as an expression of positive interactions at work, has been a subject of growing interest among both researchers and practitioners for several years (Rogala, Cieślak, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the Polish literature, job crafting is sometimes referred to as 'kształtowanie pracy' (Kasprzak, Michalak, Minda, 2017; Minda, Kasprzak, 2018) or 'przekształcanie pracy' (Rogala, Cieślak, 2019). Job crafting is based on the assumption that greater employee effectiveness, but also greater job satisfaction and employee well-being, depends to a large extent on the creative potential and self-initiative of employees at each level of an organisation.…”
Section: Introductionmentioning
confidence: 99%